2008
DOI: 10.1007/s00299-008-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

Osmyb4 expression improves adaptive responses to drought and cold stress in transgenic apples

Abstract: Constitutive expression of the rice cold-inducible Osmyb4 gene in transgenic Arabidopsis (Arabidopsis thaliana) plants improves adaptive responses to cold and drought stress, most likely due to the constitutive activation of several stress-inducible pathways and to the accumulation of several compatible solutes (e.g., glucose, fructose, sucrose, proline, glycine betaine and some aromatic compounds). Although the Osmyb4 gene seems able to activate stress responsive pathways in different species, we previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 49 publications
6
108
0
1
Order By: Relevance
“…Myb tfs interact with ciselements in the promoter regions of several stress-related genes through ABA-dependent pathway of stress signalling for the upregulation of abiotic stress responsive genes. Overexpression of Myb tf results in improved drought and salt tolerance in Arabidopsis (Ding et al 2009), osmotic tolerance (Abe et al 2003), drought stress in tomato (Vannini et al 2007) and drought and cold tolerance in the apple transgenic plants (Pasquali et al 2008). Overexpression of a StMYB1R-1 transgene in potato plants improved tolerance to drought stress while not influencing significant effects on other agronomical traits (Shin et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Myb tfs interact with ciselements in the promoter regions of several stress-related genes through ABA-dependent pathway of stress signalling for the upregulation of abiotic stress responsive genes. Overexpression of Myb tf results in improved drought and salt tolerance in Arabidopsis (Ding et al 2009), osmotic tolerance (Abe et al 2003), drought stress in tomato (Vannini et al 2007) and drought and cold tolerance in the apple transgenic plants (Pasquali et al 2008). Overexpression of a StMYB1R-1 transgene in potato plants improved tolerance to drought stress while not influencing significant effects on other agronomical traits (Shin et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Three MYB proteins have been reported to be involved in response to abiotic stress in rice. For instance, overexpression of OsMYB4 significantly enhanced tolerance to chilling and freezing stress in transgenic Arabidopsis (Vannini et al 2004;Pasquali et al 2008). Ma et al (2009) reported that OsMYB3R-2 participated in cold signalling pathway by targeting the cell cycle and a putative DREB/CBF.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…Arabidopsis transgenic plants overexpressing OsMYB4 showed increased chilling and freezing tolerance with a dwarf phenotype (Vannini et al, 2004), the tomato transgenic showed higher tolerance to drought stress (Vannini et al, 2007), whereas increased drought and cold tolerance was observed in the apple transgenic (Pasquali et al, 2008). Overexpression of a StMYB1R-1 transgene in potato plants improved plant tolerance to drought stress while having no significant effects on other agricultural traits (Shin et al 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%